The Role of Mental Health in the Medical Performance of MBBS Students - Venkteshwar, Abhishek; Maney, Kiran (Migration Letters, 2024)
Mental health (MH) and emotional intelligence (EI) have experienced significant growth in the past decade. These terms wield considerable influence over various aspects of human life. Academic achievement serves as a pivotal indicator of a student’s progress in medical education. The theoretical underpinning of this study is grounded in Waverick’s (2006) model of emotional intelligence and mental health. The research endeavors to explore the intricate relationship between EI, MH, and academic performance among MBBS students. A thorough review of literature spanning from 2010 to 2020, covering a decade, was conducted. Twenty-five research articles were scrutinized to identify gaps in the existing research. A conceptual model was constructed, and a research objective was delineated. Hypotheses were formulated in alignment with the study’s objective. This empirical investigation is based on a sample comprising 1060 MBBS students from various regions in India, employing stratified sampling. The Warwick-Edinburgh Emotional Intelligence Scale (ɑ=.0.887) was adapted, refined, and employed to collect responses related to both EI and MH from the participants. Pearson’s correlation analysis reveals a direct relationship between academic performance and the combined impact of EI and MH (r=.870). The study implies that both EI and MH exert a substantial influence on academic achievement. These findings bear relevance for students, educators, professors, mentors, consultants, and parents seeking to comprehend the pivotal role of both EI and MH in academic pursuits. It is recommended that educational authorities consider incorporating both EI and MH as subjects for medical students to enhance both academic performance and overall quality of life. Both EI and MH prove to be effective and essential for success in any profession. Given that students navigate the emotions of faculty, non-teaching staff, peers, and family, cultivating emotional management skills, alongside a robust mental health framework, is imperative for fostering a healthier, more productive, and rewarding life.